2018
DOI: 10.1002/pssr.201800317
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitecture: Toward Quantum‐Size Tuning of Superconductivity

Abstract: Quantum confinement is known to affect a nanosized superconductor through quantum‐size variations of the electronic density of states. Here, it is demonstrate that there is another quantum‐confinement mechanism overlooked in previous studies. In particular, it is found that the electron–electron attraction can be enhanced due to quantum‐confinement modifications of electronic wave functions. The superconducting correlations are strengthened by such quantum mechanical effect, which creates a subtle interplay wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Formation of thin-film lead electrodes with thicknesses from 50 nm to 200 nm was carried out by thermal evaporation in vacuum. The critical temperature of bulk lead is Т с (Pb 3D ) = 7.2 K. However, in the form of a thin film, the critical temperature of a superconductor can differ significantly from the tabulated value [ 15 16 ]. In our samples, the critical temperature of lead electrodes varied from 7.8 K < T c (Pb film ) < 8.2 K. Submicron PDP films were prepared by centrifuging the polymer from a solution in cyclohexanone on a solid substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Formation of thin-film lead electrodes with thicknesses from 50 nm to 200 nm was carried out by thermal evaporation in vacuum. The critical temperature of bulk lead is Т с (Pb 3D ) = 7.2 K. However, in the form of a thin film, the critical temperature of a superconductor can differ significantly from the tabulated value [ 15 16 ]. In our samples, the critical temperature of lead electrodes varied from 7.8 K < T c (Pb film ) < 8.2 K. Submicron PDP films were prepared by centrifuging the polymer from a solution in cyclohexanone on a solid substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Superconducting correlations in nanofilms under the enhanced electron‐electron attraction due to quantum‐confinement modifications of electronic states in interplay with surface‐substrate phonon changes were investigated by Konstantin Arutyunov et al The combined effect was shown to be controllable by the geometry of the nanostructures. The calculations agreed with the experimental size dependence of the critical temperature in high‐quality aluminum nanofilms with the size of crystallites comparable to the film thickness.…”
Section: Conjunction Between Theory and Experimentsmentioning
confidence: 99%
“…Superconductivity in reduced dimensional materials is a promising route for investigating the intricate interplay between electronic confinement and superconducting states * Author to whom any correspondence should be addressed. [1,2]. The transition from bulk materials, which are three-dimensional in nature, to their lower-dimensional counterparts like two-dimensional (2D) materials [3][4][5], onedimensional nanowires [6][7][8][9], and quantum dots [10,11] has a profound influence on superconducting behavior, owing to the effects of quantum confinement.…”
Section: Introductionmentioning
confidence: 99%